1983
DOI: 10.1073/pnas.80.14.4408
|View full text |Cite
|
Sign up to set email alerts
|

Role for the 3' end of the genome in determining disease specificity of Friend and Moloney murine leukemia viruses.

Abstract: To probe the genetic basis of disease specificity of nondefective murine type C viruses, we are constructing recombinants in vitro between molecular clones of Friend murine leukemia virus (Fr-MuLV) and Moloney murine leukemia virus (Mo-MuLV). Fr-MuLV induces erythroleukemias when injected into newborn NFS mice, whereas Mo-MuLV almost invariably induces T-cell lymphomas. We find that a recombinant whose genome is derived primarily from Fr-MuLV but which has 621 nucleotides of Mo-MuLV information at its 3' end i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
143
0

Year Published

1985
1985
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(150 citation statements)
references
References 23 publications
7
143
0
Order By: Relevance
“…It has long been speculated that the ability of Moloney MLV to cause lymphomas is due to the successful replication of the virus in lymphoid tissue (Jaenisch 1979;Chatis et al 1983;Evans and Morrey 1987;Speck et al 1990). The ability of the retroviral LTR to exploit a lymphoid transcription factor would explain in part this success.…”
Section: ~Fllelltdks-cqsfis~tg-dgwe-fklsdpde~arr~skrknkpkmnyeklsrglrymentioning
confidence: 99%
“…It has long been speculated that the ability of Moloney MLV to cause lymphomas is due to the successful replication of the virus in lymphoid tissue (Jaenisch 1979;Chatis et al 1983;Evans and Morrey 1987;Speck et al 1990). The ability of the retroviral LTR to exploit a lymphoid transcription factor would explain in part this success.…”
Section: ~Fllelltdks-cqsfis~tg-dgwe-fklsdpde~arr~skrknkpkmnyeklsrglrymentioning
confidence: 99%
“…This recombinant will grow as an infectious though less efficient virus on 3T6 cells following DNA transfection (23). As the lymphotropism of Mo-MuLV is known to be associated with its LTR sequence (24), it was rationalized that the enhancer region within this LTR may function as a lymphotropic element. However, it was found that this recombinant virus had a tissue specificity for replication in the pancreas.…”
mentioning
confidence: 99%
“…Moloney MuLV induces T-cell lymphomas, whereas Friend MuLV induces erythroleukemia when injected into newborn mice (54,65). Using recombinant viruses, disease tropism was mapped to the viral LTR (5,6). Further studies demonstrated that specific enhancer sequences within the Moloney MuLV LTR in cooperation with unique T-cell transcription factors were the primary determinants for the distinct cell tropism (3,42).…”
Section: Discussionmentioning
confidence: 99%